Alcoholic foamy degeneration and alcoholic fatty liver with jaundice: Often overlooked causes of jaundice and hepatic decompensation that can mimic alcoholic hepatitis. Issue 6 (21st January 2016) - Roth, Nitzan; Kanel, Gary; Kaplowitz, Neil
Abstract : Watch a video presentation of this article Watch the interview with the author